The Role of Nurses in Improving Medication Adherence Among Pulmonary Tuberculosis Patients: A Phenomenological Study - Syahrir, Syahrir; Ninef, Violin Irene; Bhwa, Daeng Agus Vieya Putri; Suluamu, Muliyati; Jesus, Babelonia L H De (INDOGENIUS, 2025)
Background: Tuberculosis (TB) remains a significant public health issue, particularly in developing countries, due to low treatment adherence, which can lead to drug resistance and treatment failure. Nurses play a critical role in enhancing medication adherence among pulmonary TB patients through education, monitoring, and emotional support. Objective: This study aims to explore the role of nurses in improving medication adherence among pulmonary tuberculosis patients using a phenomenological approach. Method: This qualitative study employed a phenomenological design to understand the lived experiences of nurses A total of 10 nurses from Sikumana Health Center in Kupang City, East Nusa Tenggara, who had worked for at least one year in TB treatment units, were selected using purposive sampling. Data were collected through in-depth, semi-structured interviews and analyzed using thematic analysis. Results: The findings revealed that nurses play a central role in patient education through one-on-one counseling, group discussions, and the provision of educational materials. Adherence monitoring was conducted through home visits and follow-up appointments, accompanied by emotional support and encouragement. Furthermore, nurses collaborated closely with patients' families and community health workers to foster a supportive environment that promotes treatment success. Three main themes emerged: patient education and counseling, monitoring and emotional support, and collaboration with families and communities. Conclusion: Nurses at Sikumana Health Center play a strategic role in improving medication adherence among pulmonary TB patients through educational efforts, active monitoring, and psychosocial support. Strengthening nurses' capacity and implementing supportive policies are essential to enhance treatment outcomes and prevent drug resistance.